Shadow economy in Palestinian territories using currency demand approach - Mohammad Kamal Abuamsha; S. Shumali (Journal of Economics, Finance and Administrative Science, 2022)
Purpose - The study aims at estimating the shadow economy (SE) using the method of demand for currency in Palestine for the period 2008-2018 by studying the relationship between a group of variables that affect the ratio of money traded outside the banking system to the money supply in the broad sense. Design/methodology/approach - The study has adopted analytical and descriptive research methods to estimate SE in Palestinian territories. The data has been obtained from the inflation reports issued by the Palestinian Monetary Authority for ten years, from 2008 to 2018. A standard model was constructed using EViews version 8 for statistical data processing after converting the annual data to quarterly data. Findings -The authors demonstrated that the size of the SE in Palestinian territories has varied over time, and the annual average of its size during the study period reached about 1764.893 (in millions). This amount constitutes about 15.5% of the gross domestic product. The study provides recommendations for reducing the size of the SE in Palestinian territories. Practical implications - The current study shows that shadow economics could significantly matter for economic policy design by policymakers. Originality/value - This study deals directly with Tanzi's "estimation of shadow economy in Palestinian territories" concept and its impact on economic policies.
Keywords: 330; Shadow economy; Broader money supply; M2; Taxes; Currency demand; Palestinian territories